Owner preference for insulin delivery device and glycaemic control in diabetic dogs. (31st October 2022) - Del Baldo, F.; Colajanni, L.; Corradini, S.; Palagiano, P.; Di Cunzolo, A.; Perissinotto, L.; Drudi, I.; Horspool, L.; Fracassi, F.
Abstract : Objectives: To assess treatment satisfaction and owner preference for two delivery devices (VetPen, MSD Animal Health, and U40 insulin syringes) and the effect on glycaemic control in diabetic dogs treated with porcine insulin zinc suspension. Materials and Methods: Randomised prospective cross‐over study with two arms, each of 8 weeks. Twenty client‐owned diabetic dogs on insulin treatment by U40 syringe were enrolled. Dogs were randomly assigned to receive insulin by syringe or pen injector for 2 months, followed by 2 months of the other injection method. Treatment satisfaction and owners' insulin delivery device preference were assessed using a questionnaire. Glycaemic control was assessed using a clinical score, serum fructosamine and glycated haemoglobin (HbA1c%) at the time of the enrolment (T0) and the end of each arm of treatment (T2 and T4). Results: Treatment satisfaction differed for the two types of the delivery device when the order that each device was used was taken into consideration. Owners who used the syringe first did not have a significant preference for an injection device. In contrast, owners who used the pen injector first expressed a significant preference for VetPen compared to syringes. No significant differences in the number of dogs of Groups 1 and 2 with good and poor glycaemic control at T2 and T4 were detected. Clinical Significance: Overall treatment satisfaction and preference for the two delivery methods were similar. However, VetPen was preferred by owners who were randomised to use this device first. Glycaemic control did not appear to be affected by the insulin delivery device used.